Au nanoparticles modified CuO nanowireelectrode based non-enzymatic glucose detection with improved linearity - Mishra A.K.; Jarwal D.K.; Mukherjee B.; Kumar A.; Ratan S.; Tripathy M.R.; Jit S. (My University, 2025)
This paper explores gold nanoparticle (GNP) modified copper oxide nanowires(CuO NWs)based electrode grown on copper foil for non-enzymatic glucose detection in a wide linear ranging up to 31.06 mM, and 44.36 mM at 0.5 M NaOH and 1 M NaOH concentrations. The proposed electrode can be used to detect a very low glucose concentration of 0.3 µM with a high linearity range of 44.36mM and sensitivity of 1591.44 µA mM−1 cm−2. The electrode is fabricated by first synthesizing Cu (OH)2 NWs on a copper foil by chemical etching method and then heat treatment is performed to convert Cu (OH)2 NWs into CuO NWs. The GNPs are deposited on CuO NWs to enhance the effective surface-to-volume ratio of the electrode with improved catalytic activity. The surface morphology has been investigated by XRD, XPS, FE-SEM and HR-TEM analysis. The proposed sensor is expected to detect low-level of glucose in urine, and saliva. At the same time, it can also be used to measure extremely high sugar levels (i.e. hyperglycemia) of ~ 806.5454 mg/dl. The proposed sensor is also capable of detecting glucose after multiple bending of the GNP modified CuO NWs electrode. The proposed device is also used to detect the blood sugar level in human being and it is found that this sensor’s result is highly accurate and reliable. © 2020, The Author(s).